Fertigation : the effect of irrigation regime, nitrogen source and pulse stage on the redistribution of applied nitrogen in orchard soils - Fuller, Keith (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1989.